Formation and microbial decomposability of new leaf- and root-derived soil organic carbon in forests varied with soil depth and duration: Direct evidence from 13C-labelled litter incubation - Song, Tianyang; Cheng, Siqi; Zhao, Xuechao; Fornara, Dario A.; Wang, Qingkui (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2025)
Litter inputs control the formation and accumulation of soil organic carbon (SOC) in terrestrial ecosystems. However, we still lack a complete understanding of how leaf and root litter inputs influence the formation and microbial decomposition of newly formed SOC. Here we used unique soil-litter (13C enriched) mesocosms in the field to explore the effects of leaf and root litter on SOC formation, and then through lab-incubation further assessed microbial decomposability of the new leaf and root litter-derived SOC. We found that the amount of new SOC from root litter was lower 34.3 %–49.2 % than leaf litter in the surface soil after two years of field incubation, but in the subsurface soils it was inversely (higher 110.2 %–688.9 %) and also in all soil depths over the three years of incubation. Furthermore, root litter-derived SOC in the surface soil increased with ongoing time. The differences in the decomposability between new root- and leaf-derived SOC had no clear pattern along with soil depth and incubation duration, but their decomposability at the first two year of field incubation (0.57 %–1.16 %) was significantly higher at the third year (0.09 %–0.29 %), suggesting that new SOC became more stable. The microbial decomposability of newly formed SOC was controlled by soil microbial biomass nitrogen and leucine aminopeptidase activity. These results indicated that the importance of leaf and root litter to new SOC formation and their decomposability varied with soil depth and incubation duration. Overall, our findings provide the direct experimental evidence that the importance of new leaf- and root-derived SOC for the formation and the decomposability of new SOC were soil depth-dependent. •Root litter formed higher new SOC than leaf litter in subsurface soils.•Root litter-derived new SOC in surface soil increased with ongoing time.•Root- and leaf-derived SOC had different decomposability, depending on soil depth.•Decomposability of new SOC was lower at the 3-year field incubation than others.•Decomposability was controlled by soil microbial biomass N and LAP activity.